Bronchiolar disorders in systemic autoimmune rheumatic diseases - Yanisa Kluanwan; Nichthida Tangnuntachai; Jay H. Ryu; Teng Moua (European Respiratory Review, 2025)
Pulmonary manifestations of systemic autoimmune rheumatic diseases (SARDs) may involve the large and small airways, lung parenchyma, pleura, respiratory muscles and thoracic cage. Bronchiolar disorders (BDs) or small airways disease (SAD) are common and may sometimes be the dominant presentation in patients with SARDs. We conducted a literature review using search terms “bronchiolitis,” “small airway diseases” and the names of individual SARDs and collated relevant articles published between January 1977 and April 2024. A summary of the incidence/prevalence, clinical manifestations, pathogenetic mechanisms, pulmonary function testing, chest imaging, histopathology and treatment options for BDs associated with SARDs is provided in this review. BDs associated with Sjögren syndrome, rheumatoid arthritis, systemic sclerosis, systemic lupus erythematosus, idiopathic inflammatory myositis, mixed connective tissue disease and ankylosing spondylitis are specifically highlighted.